2019
DOI: 10.1097/corr.0000000000000954
|View full text |Cite
|
Sign up to set email alerts
|

Partially Melted Ti6Al4V Particles Increase Bacterial Adhesion and Inhibit Osteogenic Activity on 3D-printed Implants: An In Vitro Study

Abstract: Background A porous Ti6Al4V implant that is manufactured using selective laser melting (SLM) has broad potential applications in the field of orthopaedic implants. The pore structure of the SLM porous Ti6Al4V implant allows for cell migration and osteogenic differentiation, which is favorable for bone ingrowth and osseointegration. However, it is unclear whether the pore structure and partially melted Ti6Al4V particles on a SLM porous Ti6Al4V implant will increase bacterial adhesion and, perhaps, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…polishing. Xie et al showed that discs cut from Ti6Al4V implant manufactured by using selective laser melting (SLM), had higher bacterial adhesion than polished ones [79]. It has also been suggested that metallic implants produced by laser powder-bed fusion should be polished or coated [46,47] since coating medical devices with different kinds of active agents may be equally successful [80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…polishing. Xie et al showed that discs cut from Ti6Al4V implant manufactured by using selective laser melting (SLM), had higher bacterial adhesion than polished ones [79]. It has also been suggested that metallic implants produced by laser powder-bed fusion should be polished or coated [46,47] since coating medical devices with different kinds of active agents may be equally successful [80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the rods prepared by extrusion were cut to obtain the wafers used in the experiment, which consequently caused uneven structures of the disc surface, as observed from the SEM images. Many studies have demonstrated that a rough structure is advantageous for cell adhesion and proliferation [ [24] , [25] , [26] ]. The SEM scanning results demonstrated that the TiCu/TiCuN coating was distributed in a granular form on the surface of the CFR-PEEK substrate, uniformly covering the PEEK matrix and the carbon fibre part.…”
Section: Discussionmentioning
confidence: 99%
“…This falls under the material 'contact guidance' principle, whereby the cell movement and development is affected by the surface morphology of the implant [37]. However, a recent in vitro study by Xie et al [38] suggested that the presence of the partially molten particles not only enhanced bacterial adhesion but also inhibited osteogenic activity of human bone mesenchymal stem cells, thus recommending the particles to be removed. The potential release of these particles cannot also be excluded, as suggested by Matouskova et al [18]; this may lead to an increased risk of inflammatory reactions or decreased hemocompatibility [18], or to raised metal (titanium) levels in the blood.…”
Section: Discussionmentioning
confidence: 99%